Syzygium cumini no diabetes mellitus iatrogênico em ratos: prevenção e tratamento - Zanoello, Andréia Maria (2001)
The objective of the present study was to investigate the possible antidiabetic properties of Syzygium cumini. The plant is often used in popular medicine. The first experiment evaluated the efficiency of the prophylactic use of Syzygium cumini against the diabetogenic effect of alloxan in rats. Syzygium cumini was offered as tea, prepared with plant leaves, at the concentration of 20 g/l. Animals received the tea as a substitute for water for 16 days before induction and for the following 3 days of the induction protocol. Fifteen female rats received the tea and another equally numbered group served as control, receiveing water. At days 17, 18 and 19 of the study diabetes was induced by daily administration of 60 mg/Kg of alloxan in all animals. The ingestion of the tea during 16 days had a hyperglycemic effect. Four days after the last dose of alloxan the plasma glucose levels of Syzygium cumini pretreated animals increased 48,86% in relation to pre-induction values. In the control group the post-induction increase was 177,96%. Additionally, pretreatment with the tea prevented the weight loss observed in the control group. These results indicate a protective effect of Syzygium cumini against diabetes mellitus induced by alloxan in rats. The second study was conducted to assess the antihyperglycemic effect of Syzygium cumini in an experimental diabetes model. The tea was prepared from leaves of Syzygium cumini, in the concentration of 200 g/l and administrated in a single dose of 25 ml/kg of body weight in alloxan-induced diabetic rats. The animals were submitted to an oral glucose tolerance test, one hour after tea ingestion. The tea ingestion improved glucose tolerance, decreasing acute hyperglycemia starting at 60 minutes after ingestion of glucose and contributing to the return to fasting levels, after 120 minutes of glucose load. These results demonstrate the antihyperglycemic effect of Syzygium cumini in diabetic rats, suggesting its potential use on the control of postprandial hyperglycemia in patients with diabetes mellitus type 1.